2003
DOI: 10.1590/s1519-566x2003000300017
|View full text |Cite
|
Sign up to set email alerts
|

Integração da resistência de plantas e predação por Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) para o manejo de Schizaphis graminum (Rondani) (Hemiptera: Aphididae) em sorgo

Abstract: Integration of Varietal Resistance and Predation by Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) for the Management of Schizaphis graminum (Rondani) (Hemiptera: Aphididae) on Sorghum ABSTRACT -The integration of plant resistance and biological control agent can be a viable alternative to the management of the greenbug, Schizaphis graminum (Rondani), on sorghum. Experiments were conducted to evaluate the effect of four sorghum genotypes: GR 11111 and TX 430 x GR 111 (resistants), GB 3B (moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Adults feed on plant-provided food and on honeydew and their larvae prey on a variety of soft-body arthropods (Carvalho & Souza 2000). In Brazil, C. externa was reported to occur in several agroecosystems (Souza & Carvalho 2002, Figueira et al 2003, Santos et al 2003, including coffee crops where its larvae are found to preying on mites, young caterpillars, and on pupae of Leucoptera coffeella (Guérin-Mèneville) (Lepidoptera: Lyonetiidae), the main coffee pest (Ecole et al 2002).…”
mentioning
confidence: 99%
“…Adults feed on plant-provided food and on honeydew and their larvae prey on a variety of soft-body arthropods (Carvalho & Souza 2000). In Brazil, C. externa was reported to occur in several agroecosystems (Souza & Carvalho 2002, Figueira et al 2003, Santos et al 2003, including coffee crops where its larvae are found to preying on mites, young caterpillars, and on pupae of Leucoptera coffeella (Guérin-Mèneville) (Lepidoptera: Lyonetiidae), the main coffee pest (Ecole et al 2002).…”
mentioning
confidence: 99%